Basic Rules and Reforms of the Prevailing Education System and the Islamic Education System: A Comparative Review: مروجہ نظام تعلیم اوراسلامی نظام تعلیم کے بنیادی ضوابط واصلاحات:ایک تقابلی جائزہ - Khalid, Dr. Muhammad Noman; Farooq, Dr. Muhammad Umar; Hussain, Dr. Hafiz Muhammad (Al Khadim Research Journal of Islamic Culture and Civilization, 2022)
On the one hand, the fact that the notion is gaining ground around the world that for education and religious training, it is necessary to integrate the education system with religious traditions, on the other hand, the need for it should be felt in Pakistan too Under the influence of this thinking, an education system is being formed in which Islamic traditions should be taken care of. Meanwhile, the existing institutions of modern education are suffering from many unlawfull manners from the Shariah point of view. In such a situation, it is necessary to research a few issues, with the help of which the features of a new Islamic education system can be clarified. Therefore, it is necessary to set up institutes which are well equipped with modern technology. Furthermore, the departments’ duty is to provide both religious and modern education in a perfect manner. Islam has given golden principles for the acquisition of knowledge. For instace, each gender male and female has to make available separate class envirnment. The most important step is to facilitate students to offer them time for prayers which are the basic religious practice of Islam. In addition to the above, it is needed to charge fee according to student financial capacity. The syllabus should decorate with Islamic way of teaching techniques. As a result, it will develop youth mentally and spiritually Islamic ideological. In this article, Islamic rules and the solution to the problems of modern institutions is discribed in Shariah point of view.